PENGARUH SUBSTITUSI TEPUNG UBI JALAR UNGU TERMODIFIKASI (Ipomoea batatas var Ayamurasaki ) TERHADAP KARAKTERISTIK WAFFLE - Anggarawati, Ni Kadek Ayu; Ekawati, I Gusti Ayu; Wiadnyani, Anak Agung Istri Sri (Jurnal Ilmu dan Teknologi Pangan (ITEPA); Vol 8 No 2 (2019): Jurnal ITEPA, 2019)
The study aims to determine the effect substitution of modified purple sweet potato flour on the characteristics of waffle and to know the best substitution of modified purple sweet potato flour with pregelatinization. The study design used was randomized group design with the treatment substitution of modified purple sweet potato flour and wheat flour, which consists of 6 levels such as: 0% : 100%, 20% : 80%, 40% : 60%, 60% : 40%, 80% : 20%, 100% : 0%. The treatment was repeated 3 times to obtained 18 units of the experiment. The data were analysed by analysis variance and if the treatment had an effect on the variable then continued with Duncan test. The result showed substitution of modified purple sweet potato flour and wheat flour had a significant effect on the content of ash, crude fiber, antioksidan capacity, texture, criteria hedonic and skor of colour, texture  and taste. Substitution of modified purple sweet potato flour 100% had the best characteristics, with 41,84% water content, 1,94% ash content, 7,17% coarse fiber content, 81,65 (mg GAEAC/kg) antioksidan capacity, 1,64 N texture, criteria skor colour dark brown, texture soft, taste of purple sweet potato very strong  and criteria hedonic colour, aroma, texture, taste and overall acceptance were like.